Imperfectly observable commitments in n-player games - Werner Güth; Georg Kirchsteiger; Klaus Ritzberger (Institute for Advanced Studies (IHS), 1996)
In a two-stage extensive form game where followers can observe moves by leaders only with noise, pure subgame perfect Nash equilibria of the limiting game without noise may not survive arbitrarily small noise. Still, for generic games, there is always at least one subgame perfect equilibrium outcome of the game with no noise that is approximated by equilibrium outcomes of games with small noise. This, however, depends crucially on generic payoffs.
Keywords: C72; 330; commitments; imperfect observability; subgame perfection